2006
DOI: 10.1176/appi.ps.57.8.1094
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Use of Concomitant Psychotropic Medications to Treat Schizophrenia in the CATIE Trial

Abstract: Concomitant use of psychotropic medications to treat people with schizophrenia is common. Empirical data demonstrating the effectiveness of many of these agents for this population are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 0 publications
5
81
1
1
Order By: Relevance
“…These findings are similar to a study by Williams et al (38) that found that nearly 90% of patients with schizophrenia received some kind of psychiatric concomitant medication and the rate for antidepressants was also nearly 40%. Concomitant baseline medications for the Clinical Anti-psychotic Trials of Intervention Effectiveness trial included antidepressants: 38%, anxiolytics: 22%, lithium: 4% and other mood stabilizers: 15% (39). Our data suggest that the use of concomitant medications, including antipsychotic polypharmacy, occurs even in the earliest stages of the disease.…”
Section: Discussionmentioning
confidence: 78%
“…These findings are similar to a study by Williams et al (38) that found that nearly 90% of patients with schizophrenia received some kind of psychiatric concomitant medication and the rate for antidepressants was also nearly 40%. Concomitant baseline medications for the Clinical Anti-psychotic Trials of Intervention Effectiveness trial included antidepressants: 38%, anxiolytics: 22%, lithium: 4% and other mood stabilizers: 15% (39). Our data suggest that the use of concomitant medications, including antipsychotic polypharmacy, occurs even in the earliest stages of the disease.…”
Section: Discussionmentioning
confidence: 78%
“…The lack of evidence-based treatments for these indications is notable given the extent to which adjunctive antidepressants, mood stabilizers, anti-anxiety agents, antipsychotics, and other medications are used in typical clinical practice. 138 The discrepancy between the relatively widespread use of adjunctive psychotropic medications and the lack of evidence to support these practices reflects, in part, the quandary that clinicians face when confronted with the person who has failed to adequately respond to antipsychotic monotherapy or has additional symptoms for which antipsychotic agents are known to be ineffective. Under these circumstances, the use of non-evidence-based practices requires that the clinician be especially conscientious in documenting whether the patient is responding to the intervention and be prepared to discontinue the treatment if a desired response is not achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The Clinical Trials of Intervention Effectiveness study in the USA found that 38% of patients received at least one antidepressant (Chakos et al 2006). Himelhoch et al (Himelhoch et al 2012) reported that 37.4% of outpatient veterans with schizophrenia received an antidepressant prescription in the USA.…”
Section: Adjunctive Antidepressant Prescriptionsmentioning
confidence: 99%